High skeletal muscle mass is associated with increased serum 25(OH)D levels in elderly - Sudarma, Verawati; Halim, Lukman (Faculty of Medicine, Trisakti University, 2017)
BackgroundLow vitamin D has been associated with various health problems. Aging influences body composition, especially body fat and fat-free mass. Anthropometric measurements, such as body weight (BW), body mass index (BMI), body fat (BF), skeletal muscle mass (SMM), waist circumference (WC) and the waist-height ratio (WHtR) represent body composition which many studies proposed will influence serum vitamin D [25(OH)D]. The objective of the present study was to determine which anthropometric measurements were determinants of 25(OH)D levels in elderly.MethodsA cross-sectional study was conducted involving 126 elderly (>60 years old) men and women at Pusat Santunan Dalam Keluarga (PUSAKA) Central Jakarta centers. Anthropometric measurements [body mass index (BMI), skeletal muscle mass (SMM), body fat (BF), and waist circumference (WC)] were determined by bioelectrical impedance analysis using the Omron body composition monitor with scales (HBF-375, Omron, Japan). Fasting blood samples were taken to measure 25(OH)D level by electrochemiluminescence immunoassay. Multivariate linear regression was used to analyze the data.Results The data showed that BMI, BF, and WC were higher than recommended, while SMM and serum 25(OH)D were lower. When the analysis was done based on sex, there were significant differences in BF, SMM, WHtR, and serum 25(OH)D. In the linear regression multivariate analysis of log 25(OH)D with age and body anthropometric measurements, only SMM reached significance level (Î²=0.019; p=0.025).ConclusionsThis study demonstrated a positive association between skeletal muscle mass and serum levels of vitamin D in elderly.